Cybersecurity: perspectives from banking & capital markets, insurance and wealth & asset management sectors - Fernandes, Ana Rita Gomes Chaves (2018)
This study focus on the perspective of cybersecurity in the financial services industry namely the Banking & Capital Markets, Insurance and Wealth & Asset Management sectors. Suffering the highest costs of cybersecurity and dealing with increasing sophisticated attacks, organizations within this industry must consider cyberattacks in their strategic planning. The comparison analysis suggests that the main vulnerability appointed by the three sectors are careless employees, their lack of training as well budget constraints and minor executive support. Moreover, the Board should acknowledge itself about information security in order to establish effective preventive and reactive measures. At last, cyber insurance interest is improving within the three sectors.